Numerical investigation of obstacle location effects in bipolar plate flow channels on PEMFC performance - Hazar, Hanbey; Durak, Alperen Latif; Sevinc, Huseyin (Elsevier Sci Ltd, 2026)
Proton exchange membrane fuel cells (PEMFCs) are promising clean energy technologies, yet their application is constrained by mass transport, water management, and pressure losses. Bipolar plates (BPs) play a vital role by controlling reactant distribution, water removal, and electrochemical performance. This study numerically investigates obstacle placement in serpentine-based channels to enhance current density and net power output. A novel configuration was examined by positioning obstacles on anode and cathode plates, and for the first time, dividing plates into upper and lower halves with region-specific arrangements. Ten models with a 25 cm2 active area were analyzed using three-dimensional CFD. Results show that obstacle placement significantly impacts performance, reactant distribution, temperature, and pressure drop. Cathode-side obstacles consistently outperformed anode-side ones, underlining the cathode's dominant role in reactant utilization. The highest net power of 13.19 W was achieved with obstacles fully covering the cathode, representing a 4.67 % improvement over the conventional serpentine design. Notably, obstacles placed only on the lower halves of both plates yielded 1.35 A/cm2 current density and 0.54 W/cm2 power density, with moderate pumping losses. These findings confirm that optimized obstacle placement offers a practical strategy for improving PEMFC bipolar plate performance.
Keywords: PEMFC; Bipolar plate design; Obstacle placement; CFD; Net power output